Implementation of STEM-Based Learning through Greenhouse Effect Experiments to Improve Students' Understanding of the Global Warming Concept - Yannika Nidiasari; Yufita Fenetiruma; Natalia Steni Mamary; Kristin Seru Matonda; Nia Mangkasa; Angganeta Yenusi; Delila Malat; Supriyatna Supriyatna; Emma Yekwam; Dorsila Wandosa; Dwi Heri Prasetyo; Aji Kumbara (CV. Dharma Samakta Edukhatulistiwa, 2026)
Global warming is an important global environmental issue for students to understand since junior high school (SMP) level. However, students' conceptual understanding of this material is still relatively low because it is abstract and often presented theoretically. This study aims to determine the improvement in junior high school students' understanding of the concept of global warming through the implementation of STEM-based learning using greenhouse effect experiments. This study used a quantitative approach with a quasi-experimental design of one-group pretest–posttest type. The subjects were 11 eighth-grade junior high school students. The research instruments were conceptual understanding tests given before (pretest) and after (posttest) the treatment, as well as observation sheets for the implementation of learning. Data were analyzed using descriptive statistics and N-Gain calculations. The results showed that the average posttest score (62.73) was higher than the average pretest score (54.55). However, the N-Gain calculation result of 0.18 is in the low category. This finding indicates that the implementation of STEM-based learning through the greenhouse effect experiment can improve students' understanding of the concept of global warming, although the improvement obtained is still relatively low. Therefore, STEM-based learning needs to be implemented sustainably and combined with other learning media to increase the effectiveness of students' conceptual understanding.